Analysis of Supply Chain Performance Improvement in the Fish Processing Industry - Manggala, Panji Wira; Machfud, Machfud; Sailah, Illah (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2024)
Abstract This study aims to identify the supply chain condition of the red snapper fish processing industry, assess the supply chain performance, and recommend performance improvements based on the performance measurement results. The study was conducted in Brondong District, Lamongan Regency, East Java, Indonesia. The methods used are the Supply Chain Operations Reference (SCOR) model and the Analytical Hierarchy Process (AHP), which measure effectiveness and efficiency parameters. Data were collected through interviews and field observations with expert respondents representing fishermen, collectors, and the fish processing industry. The results showed that the supply chain performance of the fishermen, collectors, and fish processing industry was 67.52% (poor), 88.11% (average), and 95.09% (excellent). The low performance was mainly in the fish catch composition accuracy and raw material handling practices. Root cause analysis was conducted to identify the leading causes, such as poor raw material quality, high raw material costs, and low cash-to-cash cycle time. Recommendations for improvement include handling raw materials training, using better cooling technology, and accelerating debt payments. Implementing lean supply chain management with the 5S system will improve operational efficiency and final product quality. Support from all stakeholders and government is essential for successfully implementing this strategy. Further study on the impact of lean implementation on environmental and social sustainability and exploration of new technologies for efficient fish handling and processing is needed.Keywords: AHP, lean supply chain, red snapper, SCOR, supply chain performance AbstrakPenelitian ini bertujuan untuk mengidentifikasi kondisi rantai pasok industri pengolahan ikan kakap merah, menilai kinerja rantai pasok, dan merekomendasikan perbaikan kinerja berdasarkan hasil pengukuran kinerja. Penelitian dilakukan di Kecamatan Brondong, Kabupaten Lamongan, Jawa Timur, Indonesia. Metode yang digunakan adalah model Supply Chain Operations Reference (SCOR) dan Analytical Hierarchy Process (AHP) yang mengukur parameter efektivitas dan efisiensi. Data dikumpulkan melalui wawancara dan observasi lapangan dengan responden pakar yang mewakili nelayan, pengepul, dan industri pengolahan ikan. Hasil penelitian menunjukkan kinerja rantai nelayan, pengepul dan industri pengolah ikan berturut-turut adalah 67,52% (sangat kurang), 88,11% (sedang), dan 95,09% (sangat baik). Kinerja yang rendah terutama pada ketepatan jenis ikan dan penanganan bahan baku. Analisis akar masalah dilakukan untuk mengidentifikasi penyebab utama, seperti kualitas bahan baku rendah, biaya bahan baku tinggi, dan siklus kas-ke-kas lama. Rekomendasi perbaikan mencakup pelatihan penanganan bahan baku, penggunaan teknologi pendinginan yang lebih baik, dan percepatan pembayaran utang. Implementasi lean supply chain management dengan metode 5R diharapkan meningkatkan efisiensi operasional dan kualitas produk akhir. Dukungan dari semua pemangku kepentingan dan pemerintah sangat penting untuk keberhasilan penerapan strategi ini. Penelitian ini menyarankan kajian lebih lanjut tentang dampak implementasi lean terhadap keberlanjutan lingkungan dan sosial dan eksplorasi teknologi baru untuk efisiensi penanganan dan pengolahan ikan.Kata kunci: AHP, ikan kakap merah, kinerja rantai pasok, lean supply chain, SCOR